Pengaruh Sifat Kepribadian Core Self Evaluations dan Machiavellian pada Kinerja Auditor - Ni Nyoman Sri Rahayu Damayanti; Ni Putu Riski Martini; Gde Deny Larasdiputra (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2019)
Auditor performance is an audit task that is finished by the auditor at a certain time and measured by audit quality, total task that auditor had finished, and the timeliness planned. Auditor at   Purwanto, Sungkoro & Surja Public Accountant Firm did a negligence in giving an opinion for PT Indosat Tbk. They gave an opinion without enough accurate evidence. It means that the auditor performance still being an important issue in Indonesia. Core self  evaluations and machiavellian are two personality that can predict the individual performance. Core self evaluations consist of four aspects which is locus of control, emotional stability, self-esteem, and self-efficacy. All of that personality can predict the individual behavior at workplace including individual performance. This research  implemented in public accountant firm at Bali Province. Data collected by spreading the questionnaires to the respondents. The respondents are auditor who already worked  equal or more than one year. The data was analyzed using  multiple linear regression analysis. The result showed that locus of control,  emotional stability, and self-esteem had a positive and significance influence on auditor performance. On the other hand, self-efficacy and Machiavellian had a positive but not significance influence on auditor performance.